How inclusive are smallholder farmers’ access to Digital Agricultural Platforms? Lessons from the EzyAgric Digital Platform in Uganda - Ajambo, Susan (not published yet, 2024)
This study investigates the barriers to accessing digital agricultural platforms in Uganda, focusing on EzyAgric. Using a cross-sectional qualitative design, we analysed 29 scripts from focus groups, interviews, and key informants. The Rapid Inclusivity Assessment tool identified proto-personas at risk of digital exclusion, while the Digital Divide Framework provided a theoretical basis. Three main personas emerged: tech-savvy youth (low-risk), middle-income farmers (medium-risk), and older subsistence farmers (high-risk). Key barriers include financial constraints, limited digital literacy, a lack of trust, and cultural norms. Women face additional challenges, such as financial dependency and time constraints, while elderly farmers struggle with unfamiliarity with and preference for traditional methods. Recommendations include improving the infrastructure, providing targeted digital literacy training, designing user-friendly interfaces, building trust, and considering cultural norms. The study emphasises holistic, intersectional approaches and public-private partnerships to promote equitable access to digital agricultural platforms.
none
None
Keywords: digital inclusion; digital agricultural platforms; EzyAgric; women; elderly; proto-personas